Integrating Critical Thinking into Extension Programming #1: Critical Thinking Defined - Alexa J. Lamm (EDIS)
This 3-page fact sheet is the first in the Integrating Critical Thinking into Extension Programming series. It defines critical thinking to assist extension professionals in better understanding the concept. Written by Alexa J. Lamm, and published by the UF Department of Agricultural Education and Communication, April 2015.